ACIDIFICATION OF FRESHWATER ECOSYSTEMS: IMPLICATIONS FOR THE FUTURE - Burton E. (My University, 1997)
There has been a massive shift in governmental interest toward putting money into issues surrounding global change, including acidification of ecosystem. This book is the result of the 1992 Dahlem workshop with the stated objective of reviewing the knowledge base on acid rain impacts on aquatic ecosystems, highlight research questions requiring further study, and assessing the prospects for reversal of acidic deposition effects. The text is a series of review chapters with a group summary report for each unit of review chapters. Questions focused on include the following: can we differentiate between natural and anthropogenic acidification? How does acidification interact with other contaminants that affect freshwater ecosystems? How does acidification affect biota and what are the influences of biota on acidification? Are Chemical and biological changes reversiable?